Purchase Intention on E-Commerce Application: The Effectiveness of Brand Equity as Mediation - Fendy Cuandra; Jeferey Phang; Lily Purwianti; Listia Nurjanah; Stefhani Susanto (Jurnal Ragam Pengabdian, 2026)
This study examines how brand equity functions as a mediator in the relationship between electronic word-of-mouth (E-WOM), Social Media Marketing (SMM), Brand Engagement (BENG), Brand Love (BL), Brand Equity (BEQ), and Purchase Intention (PI) in e-commerce. Currently there is no research with variables mentioned above that implemented the Theory of Planned Behavior (TPB) therefore represents novelty aspect. Data evaluated from 293 e-commerce consumers is examined using PLS-SEM. Result shows that BEQ significantly mediates the effect of SMM and E-WOM on PI. While SMM and E-WOM both increase BEQ, their direct impacts on PI are shown to be irrelevant. Furthermore, it has been demonstrated that BL significantly influences both BEQ and PI, but BEQ does not have a significant effect. The findings showed the importance of BEQ in connecting SMM to consumer PI in e-commerce while using the theory of planned behavior by Ajzen (1985) in Indonesia highlighting this research gap